THE COALITION GOVERNMENT OF THE FATHERLAND FRONT POST-WAR BULGARIA AND THE STRUGGLE FOR A REGIME OF NATIONAL DEMOCRACY - Бурдяк, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes developments of the political history of Bulgaria postwar period. The author argues that the Fatherland Front, as a non-governmental organization looren political forces, that fought for the country’s liberation from fascism, strengthened its position with the arrival of the Soviet troops. The formation of a coalition government of the Fatherland Front began a rapid evolution toward left-wing radical (Communist) alternatives in the formation of the regime of people’s democracy. At the same time, the formation of the regime of people’s democracy in the country was not a democratic way. According to the author, the reasons for the formation of just such a distorted regime of people’s democracy in post-war Bulgaria was dependent on powerful external influence, the Soviet factor, the introduction of the habitual for the Soviet Union methods of struggle against "enemies of the people", elimination of multi-party system and imposing the total monopoly of one of the Communist party and its ideology.